Online Search Patterns about Vaccination: A National Study - Inês Silva Costa; Madalena Meira Nisa; Lígia M. Ferreira (Karger Publishers, 2022)
Introduction: Google Trends is an online metadata platform that measures the relative search volume of every topic in online search engines. In medical settings, this behavior has been associated with active changes in people's perceptions and search for healthcare. This study aimed to evaluate the online search patterns of Portuguese extra-program and risk-based vaccination. Methods: Analysis of the relative search volume was performed for extra-program and risk-based vaccines, in every Portuguese district between 2006 and 2021. Relative search volume was represented between 0 and 100 (highest interest in the query). Results: Rotavirus vaccine was consistently the most searched, followed by BCG and flu, the last of which, with abnormal peaks of search in November 2009 and October 2020. We registered a significant increase in the search for every vaccine in the last 5 years (p < 0.01). Particularly, during the COVID-19 pandemic, a more abrupt increase was registered for the flu vaccine, but most importantly for BCG (3,0[69,9] vs. 9,0[528,0]). Lisboa and Porto are the only Portuguese districts where percentual research is spread across all types of vaccines. On the other hand, in Portalegre, 84% of total searches correspond to BCG. Discussion and Conclusion: The recent increase in the interest in vaccination may translate into the investment of health professionals in primary prevention measures. However, the mediatic impact of pandemics is not neglectable. Health professionals must fight misinformation as it may have happened with the increasing interest in BCG, probably due to the protective association proposed with the infection by SARS-CoV-2.